2023
DOI: 10.3389/fmicb.2023.1078886
|View full text |Cite
|
Sign up to set email alerts
|

Rhizobacterial compositions and their relationships with soil properties and medicinal bioactive ingredients in Cinnamomum migao

Abstract: IntroductionRhizobacterial communities and their metabolites can affect plant growth, development, and stress resistance, as well as the biosynthesis and accumulation of bioactive compounds in medicinal plants. This relationship has been well-characterized in many medicinal herbs, although much less commonly in medicinal trees.MethodsHere, we analyzed the composition and structure of Cinnamomum migao rhizobacterial communities across nine growing regions in Yunnan, Guizhou and Guangxi, China, as well as differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 82 publications
0
6
0
Order By: Relevance
“…In DT soils ( Figure 4E ), Bryobacter (relative abundance of 1.98% and 2.85% in the DT-CK and DT-YDJ treatments, respectively; p = 0.04), Anaeromyxobacter (1.85% and 2.89% in the DT-CK and DT-YDJ treatments, respectively; p = 0.01) , Candidatus_Solibacter (1.20% and 1.82% in the DT-CK and DT-YDJ treatments, respectively; p = 0.01) , Ellin6067 (0.70% and 0.92% in the DT-CK and DT-YDJ treatments, respectively; p = 0.01), and Bacillus (0.15% and 0.56% in the DT-CK and DT-YDJ treatments, respectively; p = 0.001) were the five most differentially abundant genera; in HD soils ( Figure 4F ), Acidibacter (relative abundance of 0.64% and 0.30% in the HD-CK and HD-YDJ treatments, respectively; p = 0.04), Blastococcus (0.16% and 0.37% in the HD-CK and HD-YDJ treatments, respectively; p = 0.01) , and Mesorhizobium (0.10% and 0.27% in the HD-CK and HD-YDJ treatments, respectively; p = 0.04) were the three most differentially abundant genera. In which, a study has shown that Bryobacter and Candidatus_Solibacter in rhizosphere soil has the potential to regulate Cinnamomum migao metabolism ( Li et al, 2023 ); Ellin6067 as a kind of nitrosifying bacteria, which may participate in the soil nitrogen cycling process ( Lv et al, 2022 ); Bacillus is a well-known plant growth-promoting bacterium ( Sheng, 2005 ; Ali et al, 2021 ). Blastococcus with potential capacity improve the soil nutrient supply ( Li et al, 2022 ); Mesorhizobium be found with capacity of improves chickpea growth under chromium stress and alleviates chromium contamination of soil ( Naz et al, 2023 ).…”
Section: Resultsmentioning
confidence: 99%
“…In DT soils ( Figure 4E ), Bryobacter (relative abundance of 1.98% and 2.85% in the DT-CK and DT-YDJ treatments, respectively; p = 0.04), Anaeromyxobacter (1.85% and 2.89% in the DT-CK and DT-YDJ treatments, respectively; p = 0.01) , Candidatus_Solibacter (1.20% and 1.82% in the DT-CK and DT-YDJ treatments, respectively; p = 0.01) , Ellin6067 (0.70% and 0.92% in the DT-CK and DT-YDJ treatments, respectively; p = 0.01), and Bacillus (0.15% and 0.56% in the DT-CK and DT-YDJ treatments, respectively; p = 0.001) were the five most differentially abundant genera; in HD soils ( Figure 4F ), Acidibacter (relative abundance of 0.64% and 0.30% in the HD-CK and HD-YDJ treatments, respectively; p = 0.04), Blastococcus (0.16% and 0.37% in the HD-CK and HD-YDJ treatments, respectively; p = 0.01) , and Mesorhizobium (0.10% and 0.27% in the HD-CK and HD-YDJ treatments, respectively; p = 0.04) were the three most differentially abundant genera. In which, a study has shown that Bryobacter and Candidatus_Solibacter in rhizosphere soil has the potential to regulate Cinnamomum migao metabolism ( Li et al, 2023 ); Ellin6067 as a kind of nitrosifying bacteria, which may participate in the soil nitrogen cycling process ( Lv et al, 2022 ); Bacillus is a well-known plant growth-promoting bacterium ( Sheng, 2005 ; Ali et al, 2021 ). Blastococcus with potential capacity improve the soil nutrient supply ( Li et al, 2022 ); Mesorhizobium be found with capacity of improves chickpea growth under chromium stress and alleviates chromium contamination of soil ( Naz et al, 2023 ).…”
Section: Resultsmentioning
confidence: 99%
“…Exophiala and Clonostachys contribute to the decrease in PCH polysaccharides content, while Enterobacter may participate in the synthesis of PCH polysaccharides, thereby increasing their content. Previous studies have shown that Fusarium significantly increases the content of polysaccharides and other metabolites (Li et al, 2023). Acidibacter can promote the synthesis and accumulation of terpenoid compounds and also has a certain impact on polysaccharide compounds (Ren et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the geographical locations where the plant materials were collected can play a crucial role, as distinct regions may have unique microclimates and soil compositions, influencing the overall chemical profile of the plants [ 41 ]. Therefore, the divergence in compound composition between studies underscores the complexity of plant chemistry and highlights the importance of considering multiple factors when comparing phytochemical profiles across different studies.…”
Section: Discussionmentioning
confidence: 99%